The demand for private nursing care in Gdansk - Pilarska, Marietta; Zimmermann, Agnieszka; Banasik, Przemysław (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. The opportunity for the establishment of private nursing practices means facing the challenges related to the commercialization of health care system and to market supply conditions including the demand for their service. Aim of the study. The purpose of the study was to investigate the demand for private nursing care in Gdansk and patients’ experiences, expectations and concerns. Material and methods. A self-designed questionnaire was used, conducted in an open, voluntary and anonymous manner. One hundred patients from Gdansk were examined from October 2012 to April 2013. Results. There is significant patients interest in private nursing services (73% respondents) but in practice there is a relatively low level of take-up (39%). The main obstacles are: costs (68%) and lack of information (40%). Many patients are not aware of the existence of a private nursing services and only 29% of them associated their home as the location of the health delivery. Patients expect from the nursing services: professionalism and conscientiousness, empathy, availability of financing and flexibility. Conclusions. Analysis of the survey results, from the Gdansk based respondents indicates, a significant level of interest in private nursing services but concern regarding the cost is main obstacle to its use. Patients feel that they lack sufficient information regarding the cost, scope and availability of private nursing services. This fact should be addressed by private nursing practitioners. Efforts should be made to rise the social awareness of the role and spectrum of private nursing care in Gdansk. Nursing Topics 2014; 22 (4): 484–489